2000
DOI: 10.1128/iai.68.10.5619-5627.2000
|View full text |Cite
|
Sign up to set email alerts
|

Gallium Disrupts Iron Metabolism of Mycobacteria Residing within Human Macrophages

Abstract: Mycobacterium tuberculosis and M. avium complex (MAC) enter and multiply within monocytes and macrophages in phagosomes. In vitro growth studies using standard culture media indicate that siderophoremediated iron (Fe) acquisition plays a critical role in the growth and metabolism of both M. tuberculosis and MAC. However, the applicability of such studies to conditions within the macrophage phagosome is unclear, due in part to the absence of experimental means to inhibit such a process. Based on the ability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
238
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 211 publications
(248 citation statements)
references
References 49 publications
8
238
0
2
Order By: Relevance
“…Mononuclear cells were separated on a Ficoll (Amersham Biosciences) cushion and the PBMCs were cultured for 5 days in Teflon wells (Savillex) containing RH (RPMI medium, 20 mM HEPES, 20 mM -glutamine) plus 20 % autologous serum. The resulting MDMs were adhered to glass or plastic (see electron-microscopy section ; Waco Pure Chemical Industries) coverslips, or they were adhered directly to wells of a 24-well (Becton Dickinson Labware) or a 6-well (Corning) tissue-culture plate for 2 h. Non-adherent cells were removed from the plates by washing, and the MDMs were cultured for an additional 7 days in RH plus 20 % autologous serum, prior to the addition of Mtb (Olakanmi et al, 2000). Each experimental condition was performed with 2 donors.…”
Section: Methodsmentioning
confidence: 99%
“…Mononuclear cells were separated on a Ficoll (Amersham Biosciences) cushion and the PBMCs were cultured for 5 days in Teflon wells (Savillex) containing RH (RPMI medium, 20 mM HEPES, 20 mM -glutamine) plus 20 % autologous serum. The resulting MDMs were adhered to glass or plastic (see electron-microscopy section ; Waco Pure Chemical Industries) coverslips, or they were adhered directly to wells of a 24-well (Becton Dickinson Labware) or a 6-well (Corning) tissue-culture plate for 2 h. Non-adherent cells were removed from the plates by washing, and the MDMs were cultured for an additional 7 days in RH plus 20 % autologous serum, prior to the addition of Mtb (Olakanmi et al, 2000). Each experimental condition was performed with 2 donors.…”
Section: Methodsmentioning
confidence: 99%
“…Infected monolayers were washed and either repleted with RH containing 1% human autologous serum and further incubated for 24, 48, or 72 h or lysed (0 h time point) as described (27). After the 0 time point, the supernatant (containing detached infected MDMs) and monolayers were lysed separately and then pooled.…”
Section: Matrix-assisted Laser Desorption/ionization Time-of-flight (mentioning
confidence: 99%
“…Intracellular Growth of Strains Erdman and HN885 in Macrophages-For measurements of intracellular growth in macrophages, 12-day-old MDM monolayers were washed, and M. tuberculosis bacilli were added to MDMs (multiplicity of infection 1:1; duplicate wells) in either RH containing 2.5% serum or RHH and incubated for 2 h at 37°C in 5% CO 2 (27). Infected monolayers were washed and either repleted with RH containing 1% human autologous serum and further incubated for 24, 48, or 72 h or lysed (0 h time point) as described (27).…”
Section: Matrix-assisted Laser Desorption/ionization Time-of-flight (mentioning
confidence: 99%
“…[2] It was also shown that gallium is effective in two murine lung infection models. Other studies have demonstrated that gallium is effective against the organisms causing tuberculosis [3] and malaria [4] in human beings, and in the treatment of Rhodococcus equi caused pneumonia in foals. [5] Recently, we have shown that phosphate-based glasses (PBGs) in the system CaO-Na 2 O-P 2 O 5 system provide a means to deliver Ga 3+ ions in a controlled way.…”
Section: Introductionmentioning
confidence: 99%